2013
DOI: 10.1111/ipd.12030
|View full text |Cite
|
Sign up to set email alerts
|

Assessing salivary osmolality as a caries risk indicator in cerebral palsy children

Abstract: Osmolality exhibited a stronger association with caries occurrence than did salivary flow rate. This parameter, therefore, could be a potential caries risk indicator for spastic cerebral palsy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 20 publications
(28 reference statements)
3
50
0
9
Order By: Relevance
“…Risk factors such as present of infantile reflexes (rooting, suckle-swallow, biting and gagging) would explain this [37], as well as side effects of drugs and recurrent hospitalization [38], high salivary osmolality [39], soft diet intake [40], high frequency of carbohydrate intake, autocleaning inability; all this factor contributing to difficulty in maintaining adequate oral hygiene.…”
Section: Caries Prevalence In Children With Cpmentioning
confidence: 99%
“…Risk factors such as present of infantile reflexes (rooting, suckle-swallow, biting and gagging) would explain this [37], as well as side effects of drugs and recurrent hospitalization [38], high salivary osmolality [39], soft diet intake [40], high frequency of carbohydrate intake, autocleaning inability; all this factor contributing to difficulty in maintaining adequate oral hygiene.…”
Section: Caries Prevalence In Children With Cpmentioning
confidence: 99%
“…However, adequate oral care performance is not always achieved due to the directly proportional relationship between severity of the neurological alteration and the difficulty demonstrated by these individuals to receive adequate oral care . Thus, epidemiological studies have shown high rates of oral complaints in individuals with CP …”
Section: Introductionmentioning
confidence: 99%
“…19 Este fato pode sugerir que a experiên-cia de cárie nesses indivíduos está relacionada com o quadro sistêmico, o qual influencia negativamente a função intelectual e a coordenação motora através da presença de movimentos involuntários, reflexos orais patológicos e espasticidade dos músculos da mastigação, dificultando, assim, a realização e o recebimento de uma prática de higiene bucal eficaz e interferindo na consistência da dieta. 6,7,19,20,25,27 A elevada experiência de cárie pode ser explicada ainda pela presença de desigualdade social, que é um fator determinante. 6,20,22 As crianças e adolescentes com paralisia cerebral apresentaram elevada prevalência de alterações periodontais.…”
Section: Discussionunclassified
“…[3][4][5] Pacientes com paralisia cerebral tem apresentado, então, maior risco de desenvolver cárie dentária e doença periodontal. [6][7][8] Outros fatores, como condições socioeconômicas, consistência líquida da dieta, osmolaridade salivar e maior grau de dano neurológico também podem constituir riscos para os problemas de saúde oral. 3,9 Além disso, alterações estruturais na região orofacial, déficits neuromusculares e hábitos parafuncionais podem dar origem a diversos problemas dentários como má oclusão, salivação excessiva e bruxismo.…”
Section: Introductionunclassified